The Influence of Competency, Career Development, and Work-Life Balance on Job Satisfaction of Library Staff in Bangka Belitung Province - Gladia, Shellia; Reniati, Reniati; Sumar, Sumar (FEB - Universitas Lampung, 2024)
This research aims to analyze the influence of competency, career development, and work-life balance on job satisfaction among library staff in the Bangka Belitung Islands Province. This research includes quantitative descriptive research using survey methods with a sample size of 180 people. The data analysis method used is multiple linear regression analysis using the t test, f test and analysis of the coefficient of determination (R2). The research results obtained are that competency partially has no significant effect on job satisfaction, career development partially has a positive and significant effect on job satisfaction, work-life balance partially has a positive and significant effect on job satisfaction. Meanwhile, simultaneously, competency, career development and work-life balance have a positive and significant influence on job satisfaction among library staff in the Bangka Belitung Islands Province. Meanwhile, the results of the coefficient determination analysis (R2) show an R Square figure of 0.383 or 38.3%.